Superovulation and embryo recovery in Ongole cows using different FSH preparations - RAO, K BABU; RAO, M MUTHA; RAJU, M S (The Indian Journal of Animal Reproduction, 2023)
Fifteen parous Ongole breed cows were repeatedly superovulated for 23 times using two Follicle Stimulating Hormone (FSH) preparations - the Super ov and the Folltropin. 82.6 percent animals responded to superovulation. A total of 46 embryos were collected non-surgically of which 27 were viable. Among the animals responded to superovulation the overall mean ovulation rate, total and viable embryo recovery rates were 9.68±1.79, 2.42±1.29 and 1.42±1.00 respectively. There was a significant (P>-0.01) difference between groups in the mean ovulation rate and the mean total and transferable embryos.